(untitled) (Journal of Nobel Medical College, 2020)
Background: A wound is an injury caused by a cut, blow, or any else that typically involves laceration. For the treatment of infections and promoting wound healing, povidone-iodine is usually used but sometimes it can lead to irritation. The researcher would like to develop Lansium domesticum Corr. (duku) seed extract ointment to promote wound healing. Materials and Methods: This experimental study was done on 30 rats which are divided into six groups namely negative control, positive control (povidone-iodine 10%), the experimental group with three different concentration of Lansium domesticum seed extract ointment (2.5%, 5%, and 10%) and followed for three days to assess wound size. Approval was acquired by the Research Ethics Committee of the Sriwijaya University Faculty of Medicine, Palembang, Indonesia. In vitro capacity of Lansium domesticum extract also assessed by measuring inhibitory diameter. Results: After three days of treatment, there is a significant difference in wound closure for all groups (p<0.05) except for the negative control group. The best wound closure was found in a 10% extract group with average wound size decreasing by 0.3 cm. For in vitro activity, only 10% Lansium domesticum seed extract ointment which is showing inhibitory zone at 3 mm of diameter. Conclusion: Lansium Domesticum Corr. seed extract ointment has the potency to promote wound healing on rats in addition to its small antimicrobial activity.